Medan Makna Rasa dalam Bahasa Melayu Dialek Jakarta - Darsita Darsita (Buletin Al-Turas, 2006)
A sense of field experience of Betawi peopke in daily dialect (Bahasa Melayu Dialek Jakarta/BMD) is expressed by body language (the five senses, link, body, part of the body, etc...)